The Criminal mediation, ¿a model of the restorative justice in the criminal law system? (2010)
The scope of this work is firstly to show a general overview on restorative justice as the new paradigm on the understanding of Criminal law and its possible adequacy on the construction of the aims and roles formally built by Doctrine. Secondly, it tries